THE ROLE OF PRELIMINARY HEARINGS IN JAPANESE COURTS. - Sadriddinzoda Sitora Shakhobiddinovna (International Journal of Literature and Language Studies, 2026)
This article discusses the legal document adopted for the introduction of the institution of preliminary hearings in Japan, the significance of this document in the practice of administrative courts, as well as the procedure for conducting preliminary hearings in administrative courts of this country. Also, the general aspects of the application of the initial institute in foreign countries and some important cases in judicial practice are highlighted, foreign and national legislation is comparatively studied, and information on the relevance of introducing this institute into our judicial practice is included.